Exponential repulsion improves structural predictability of molecular docking. Issue 28 (13th September 2016) - Bazgier, Václav; Berka, Karel; Otyepka, Michal; Banáš, Pavel
Abstract : Molecular docking is a powerful tool for theoretical prediction of the preferred conformation and orientation of small molecules within protein active sites. The obtained poses can be used for estimation of binding energies, which indicate the inhibition effect of designed inhibitors, and therefore might be used for in silico drug design. However, the evaluation of ligand binding affinity critically depends on successful prediction of the native binding mode. Contemporary docking methods are often based on scoring functions derived from molecular mechanical potentials. In such potentials, nonbonded interactions are typically represented by electrostatic interactions between atom‐centered partial charges and standard 6–12 Lennard–Jones potential. Here, we present implementation and testing of a scoring function based on more physically justified exponential repulsion instead of the standard Lennard–Jones potential. We found that this scoring function significantly improved prediction of the native binding modes in proteins bearing narrow active sites such as serine proteases and kinases. © 2016 Wiley Periodicals, Inc. Abstract : This study presents implementation and testing of scoring function based on AMBER force field with AMBER‐like arithmetic mixing rules and more physically justified exponential repulsion instead of standard 6–12 Lennard–Jones potential. Several robust tests showed that the scoring function with exponential repulsion improves prediction of native binding poses in proteins bearing narrow and polar active sites such as serine proteases and kinases.